Bone marrow fibroblasts overexpress miR‐27b and miR‐214 in step with multiple myeloma progression, dependent on tumour cell‐derived exosomes. Issue 2 (22nd January 2019) - Frassanito, Maria Antonia; Desantis, Vanessa; Di Marzo, Lucia; Craparotta, Ilaria; Beltrame, Luca; Marchini, Sergio; Annese, Tiziana; Visino, Fabrizio; Arciuli, Marcella; Saltarella, Ilaria; Lamanuzzi, Aurelia; Solimando, Antonio G; et al.
Abstract: Aberrant microRNA (miR) expression has an important role in tumour progression, but its involvement in bone marrow fibroblasts of multiple myeloma patients remains undefined. We demonstrate that a specific miR profile in bone marrow fibroblasts parallels the transition from monoclonal gammopathy of undetermined significance (MGUS) to myeloma. Overexpression of miR‐27b‐3p and miR‐214‐3p triggers proliferation and apoptosis resistance in myeloma fibroblasts via the FBXW7 and PTEN/AKT/GSK3 pathways, respectively. Transient transfection of miR‐27b‐3p and miR‐214‐3p inhibitors demonstrates a cooperation between these two miRNAs in the expression of the anti‐apoptotic factor MCL1, suggesting that miR‐27b‐3p and miR‐214‐3p negatively regulate myeloma fibroblast apoptosis. Furthermore, myeloma cells modulate miR‐27b‐3p and miR‐214‐3p expression in fibroblasts through the release of exosomes. Indeed, tumour cell‐derived exosomes induce an overexpression of both miRNAs in MGUS fibroblasts not through a simple transfer mechanism but by de novo synthesis triggered by the transfer of exosomal WWC2 protein that regulates the Hippo pathway. Increased levels of miR‐27b‐3p and miR‐214‐3p in MGUS fibroblasts co‐cultured with myeloma cell‐derived exosomes enhance the expression of fibroblast activation markers αSMA and FAP. These data show that the MGUS‐to‐myeloma transition entails an aberrant miRNA profile in marrow fibroblasts and highlight a key role of myeloma cells in modifying the bone marrow microenvironment by reprogramming the marrow fibroblasts' behaviour. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.